2015 23rd Telecommunications Forum Telfor (TELFOR) 2015
DOI: 10.1109/telfor.2015.7377529
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layer 5G mobile phone antenna for multi-user MIMO communications

Abstract: In this study, a new design of multi-layer phased array antenna for millimeter-wave (mm-Wave) fifth generation (5G) mobile terminals is proposed. The proposed linear phased array antenna is designed on four layers of the Rogers RT5880 substrates to operate at 28 GHz which is under consideration for 5G wireless communications. Two identical linear sub arrays can be simultaneously used at different sides of the mobile-phone printed circuit board (PCB) for operation in diversity or multiple-input multiple-output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 5 publications
0
31
0
Order By: Relevance
“…CONCLUSION This paper proposed designs for 5G mobile-phone antenna at 21.5 GHz of frequency.Their S 11 , VSWR, polar plots and radiation patterns showed that they can be used as 5G antennas. In future these antenna designs can be applied with phase shifters so that beam can be steered itself as the user moves [2].This will help to achieve peak data rate and high gain beams from various directions [4].…”
Section: ) U Shape Antenna Arraymentioning
confidence: 99%
“…CONCLUSION This paper proposed designs for 5G mobile-phone antenna at 21.5 GHz of frequency.Their S 11 , VSWR, polar plots and radiation patterns showed that they can be used as 5G antennas. In future these antenna designs can be applied with phase shifters so that beam can be steered itself as the user moves [2].This will help to achieve peak data rate and high gain beams from various directions [4].…”
Section: ) U Shape Antenna Arraymentioning
confidence: 99%
“…The switched‐beam phased array antennas are used in emerging wireless applications including modern radars, biomedical and satellite systems . The switched‐beam antennas are an integral part of a promising keyless physical layer security technique termed as directional modulation (DM) to transmit the digitally modulated information signals in a prespecified secure wireless communication spatial direction in free space .…”
Section: Introductionmentioning
confidence: 99%
“…This technology is a key component and probably the most established to truly reach the promised transfer data rates of fifth generation (5G) communication systems [4,5]. MIMO antennas are important for increasing channel capacity and link reliability [6,7]. Standard MIMO networks tend to use two or four antennas in a single physical package.…”
Section: Introductionmentioning
confidence: 99%